The rejection of theodicy in the work of Emmanuel Lévinas - Maidan, Michael (2017)
This paper reviews Lévinas’ understanding of evil and his rejection of any form of theodicy, in the light of the reintroduction of the question of evil in political discourse and in contemporary philosophical thought.